Juan Manuel, Ordenamjentos dados a la villa de Peñafiel, 10 de abril de 1345. A reconstruction of the manuscript text with an introduction and annotated English translation by Richard P. Kinkade. Hispanic Seminary of Medieval Studies, Madison, 1996; xvii + 143 pp. (Spanish Series, 112). - Laurette Godinas (Nueva Revista de Filología Hispánica, 1997)
Se reseñó el libro: Ordenamjentos dados a la villa de Peñafiel, 10 de abril de 1345.